Pelanggaran Kode Etik Profesi Aparat Kepolisian yang Melakukan Kekerasan Terhadap Pengunjuk - Susanto, Yokki; Yusuf, Hudi (Media Hukum Indonesia (MHI), 2025)
In the 1945 Constitution of the Republic of Indonesia Article 28 states that "freedom of association and assembly, expressing thoughts verbally and in writing and as stipulated in the law, which is ratified by the birth of Law No. 9 of 1998 concerning Freedom of Public Opinion in advance. The State Police as a tool given the task and responsibility to secure the implementation of demonstrations, which is also regulated in Law Number 2 of 2002 concerning the Indonesian National Police. However, the existence of this regulation does not always make the implementation of demonstrations run safely, we can actually see and hear that demonstration activities often end in clashes between demonstrators. Police officers who are proven to have committed acts of violence against protesters will be given disciplinary sanctions, a code of ethics and even be prosecuted in the General Court for taking actions that are not in accordance with procedures and the law. However, there are several factors that have not yet been implemented for the implementation of the law and criminal sanctions against police officers who commit violence against protesters, including the mental factors of law enforcers, the legal factors themselves and factors of the community who do not want to report. Therefore, the police are expected to take steps to impose criminal sanctions on police officers who commit acts of violence against protesters, including maximizing their mentality in law enforcement, understanding the law and having the initiative in enforcing the law.